PENGGUNAAN FILM ADAPTASI SEBAGAI MEDIA PENGAJARAN SASTRA - Riyadi, Sugeng (Jurnal Pendidikan Bahasa dan Sastra, 2014)
It has become a trend in film industry, either in national scope or international scope,Â  that literary works are adapted into movies. Some people think that it decreases people interest on reading literary works, which is already low, as most people tend to prefer watching the movies instead of reading the literary works. However, if we study this matter further, it is very possible that it happens the other way around. This article tries to highlight some important points of film adaptation from literary works, its possible roles in literary learning, and some practical applications of its utilization in literary learning in the classroom.